Analisis Komparasi Kinerja Keuangan Sebelum Dan Sesudah Merger Pada PT Indosat Ooredoo Hutchison Tbk Periode 2019 – 2024 - Annisa Dalimunthe; Fikron Al-Choir (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Abstract. This study aims to determine the differences in financial performance at PT Indosat Ooredoo Hutchison Tbk for the 2019-2024 period before and after the merger, as measured by the Current Ratio, Debt to Asset Ratio, Net Profit Margin, and Total Asset Turn Over. The research method used is a quantitative method with a comparative approach. Data analysis techniques in this study used descriptive statistical analysis, normality tests, and the Paired Sample t-Test and Wilcoxon Signed Rank Test using SPSS. The results of this study indicate that partially, there is no significant difference in the Current Ratio with a significance value of 0.136 > 0.05. For the Debt to Asset Ratio, there is a significant difference with a significance value of 0.024 < 0.05. For the Net Profit Margin, there is no significant difference with a significance value of 0.388 > 0.05. Furthermore, for the Total Asset Turn Over, there is no significant difference with a significance value of 0.178 > 0.05. The conclusion of this study indicates that the merger policy only provides a significant influence on reducing the company's debt ratio (solvability).